1993
DOI: 10.1080/17450399309386058
|View full text |Cite
|
Sign up to set email alerts
|

Study on the energy and protein requirements in goats

Abstract: The present study focussed on the energy and protein metabolism in pregnant and lactating goats, including young female goats up to 8 months of age, in order to determine feed availability, as also the energy and protein requirements. It was found that the diets consisting of alfalfa hay, oats hay, maize, wheat bran and mixed feeds (fed to suckling females) had different availabilities in terms of energy and protein, according to animal physiological condition and age. Thus, in pregnant goats, 21% of the metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
2
1
Order By: Relevance
“…In addition, the observed NE m (197 kJ/kg EBW 0.75 ) was also lower than those reported for sheep of 269 (Rattray et al, 1973) and 259 kJ/kg BW 0.75 (Blaxter, 1967). The ME m found in this study were considerably lower than those previously reported for goats: 400 kJ/kg BW 0.75 for pregnant and lactating goats up to 8 mo of age (Voicu et al, 1993), 438 kJ/kg BW 0.75 for mature goats (AFRC, 1998), 462 kJ/kg BW 0.75 for mature goats over 18 mo of age (Luo et al, 2004b), 501 kJ/kg BW 0.75 for mature dairy goats (NRC, 2007), and 542 kJ/kg BW 0.75 for mature and growing goats (Salah et al, 2014).…”
Section: Energy Requirements For Maintenancecontrasting
confidence: 90%
“…In addition, the observed NE m (197 kJ/kg EBW 0.75 ) was also lower than those reported for sheep of 269 (Rattray et al, 1973) and 259 kJ/kg BW 0.75 (Blaxter, 1967). The ME m found in this study were considerably lower than those previously reported for goats: 400 kJ/kg BW 0.75 for pregnant and lactating goats up to 8 mo of age (Voicu et al, 1993), 438 kJ/kg BW 0.75 for mature goats (AFRC, 1998), 462 kJ/kg BW 0.75 for mature goats over 18 mo of age (Luo et al, 2004b), 501 kJ/kg BW 0.75 for mature dairy goats (NRC, 2007), and 542 kJ/kg BW 0.75 for mature and growing goats (Salah et al, 2014).…”
Section: Energy Requirements For Maintenancecontrasting
confidence: 90%
“…Regarding to the biochemical alterations in goats with pregnancy toxemia, in the present study, we founded that there is a significant reduction in the serum glucose level in goats with PT, which may be attributed to decrease in the hepatic gluconeogenesis (Mills et al, 1986), with increase the energy requirements of the pregnant goats that carries two feti (Voicu et al, 1993), also decrease the endogenous glucose production may be developed as a result of decrease calcium levels, which occur during the period of pregnancy (Schlumbohm and Harmeyer, 2003), and may be due to the hyperketonemia produces adverse effect onenergy balance and glucose metabolism (Harmeyer and Schlumbohm, 2006). These results were in agreement with (Hefnawy et al, 2010;Gonza´ lez et al, 2011;Abdelaal et al, 2013).…”
Section: Discussionmentioning
confidence: 91%
“…In addition, litter weight can be roughly estimated from the sheep equations of ARC (1980). Alternatively, DLG (2003) published equations that describe the course of foetal development during the last third of pregnancy from data obtained by Voicu et al (1993) in Carpathian goats.…”
Section: Prediction Of Body Weight Growth Rate and Foetal Developmentmentioning
confidence: 99%